Vitamin B6 Alleviates Lipopolysaccharide-induced Myocardial Injury by Ferroptosis and Apoptosis Regulation - Shan, Meirong; Yu, Xujie; Li, Yajie; Fu, Changning; Zhang, Cheng (Frontiers in Pharmacology, 2021)
Vitamin B6 (VitB6) is a water-soluble vitamin and includes pyridoxine, pyridoxal, pyridoxamine, and their phosphorylated forms. In the current study, we demonstrated that VitB6 could improve lipopolysaccharide (LPS)–induced myocardial injury. We demonstrated that VitB6 can suppress LPS-induced oxidative stress and lipid peroxidation that lead to ferroptosis and apoptosis in vivo and in vitro. Moreover, we found that VitB6 can regulate the expression of iron regulatory proteins, maintaining intracellular iron homeostasis. To confirm that VitB6 could inhibit LPS-induced ferroptosis and apoptosis, we pretreated mice with ferrostatin-1 (Fer-1) and emricasan that efficiently mimicked VitB6 pharmacological effects. This improved the survival rate of mice challenged with a high LPS dose. In addition, VitB6 regulated the expression of LPS-induced apoptosis-related proteins and iron regulatory proteins. It mediated the expression of Nrf2, transcription factor NF-E2–related factor 2, which promoted the expression of antioxidant enzymes and restrained LPS-induced ferroptosis and apoptosis. Overall, our results indicated that VitB6 can be used on novel therapies to relieve LPS-induced myocardial injury.